Effect of plyometric and sprint training on repeated sprint and vertical jump capacities in volleyball players aged 11 to 14 Years: A longitudinal study (Research, Society and Development, 2024)
In adults, plyometric training can positively influence repeated sprint ability, and sprint training can influence vertical jump capacity. However, in children and adolescents, such influences are not yet clear. The aim of this study was to evaluate the effect of plyometric training on repeated sprinting ability and the effect of repeated sprint training on vertical jump performance in young volleyball players of both sexes. Longitudinal study with a sample of 30 adolescents, aged 11 to 14 years. The volunteers were divided into a control group, a plyometric training group, and a sprint training group, and they underwent six weeks of training (two sessions per week). Their repeated sprint ability was assessed using photocell technology, and their vertical jump capacity was evaluated on a platform with an interruption system. There was a significant difference in pre- and post-training within the groups. The Sprint Group showed improvement in the best sprint (p=0.023) and worst sprint (p=0.10). The group that performed additional plyometric training also showed improvement in the best sprint (p=0.004) and worst sprint (p=0.008). As for the countermovement vertical jump, the Sprint Group showed a significant difference from pre-training (5.04±0.67) to post-training (5.37±0.54). The repeated sprint training proved to be effective in improving both repeated sprint and vertical jump capabilities.